Stress and strain analysis of spherical sealing cups of fluid-driven pipeline robot in dented oil and gas pipeline. (January 2020) - Zhang, Hang; Dong, Jinhui; Cui, Can; Liu, Shuhai
Highlights: A FE model of a pipeline robot with spherical sealing cups contacted with the dented pipe was built. Effects of parameters on the stress and strain of the spherical sealing cup was presented. The deformation of the cup reaches the maximum at the peak of the dent. The stress of the cup reaches the maximum at the downhill of the dent. The thickness of the cup has the greatest effect when PIG runs through the dent. Abstract: Pipeline inspection gauge (PIG), as a kind of pipeline robot, Pipeline inspections gauges (PIGs) have been the main equipment during different stages of operation to perform functions such as pigging and inner inspecting. However, due to the failure of the sealing cup, the PIG is often stuck when it runs in the oil and gas pipeline especially in dented pipe. The distribution of stress and strain on the outer edge of the spherical sealing cup is complex but rewarding for understanding the blockage problems. When the PIG is in a straight pipeline section, it can be abstracted as an interference problem between polyurethanes rubber and steel. In this study, the numerical solution and the analytical solution of the polyurethane rubber and steel interference problem was first compared with each other to verify the numerical solution. Then, effects of the interference ( δ ), thickness ( t ), and radian ( θ ) of the spherical sealing cup on the stress and strain distribution on the outer edge of the cup were discussed using MSC Marc 2016 when the PIG was in dented pipe. Results indicate that the interference of the sealing disc has the greatest impact on the stress and strain distribution when PIG runs in the straight pipeline section. However, the thickness of the sealing cup has the greatest impact on the stress and strain distribution when PIG runs through the dent. The conclusions obtained in this study are beneficial for the selection and design of the spherical sealing cups PIG.